Abstract ID: 15 Experimental verification of 4D Monte Carlo calculations of dose delivered to a deforming anatomy. (October 2017) - Cygler, Joanna E.; Gholampourkashi, Sara; Heath, Emily
Abstract : The aim of this work is to validate 4D Monte Carlo (MC) simulation method[1] for reconstructing dose delivered to a breathing patient. Static and VMAT plans were delivered to a deformable lung phantom by an Elekta Agility linear accelerator and measured doses were compared with simulations. Measurements were performed in a deformable lung phantom containing a 2.6 cm diameter tumour with the phantom in stationary and moving (sinusoidal) states. Dose within the tumor was measured using EBT3 film and a RADPOS detector connected to the RADPOS 4D dosimetry system[2] . Dose inside the lung was measured by another RADPOS detector mounted outside the tumor at 1.5 cm from the tumor center. A single 6 MV 3 × 3 cm 2 square field and a VMAT plan, both covering the tumour, were created on the end-of-inhale CT scans using Monaco V.5.10.02. A validated BEAMnrc model of our Elekta linac was used for all MC simulations. For 4D simulations, deformation vectors were generated by deformable registration of end-of-exhale to end-of-inhale 4DCT images using Velocity AI 3.2.0 as input to the 4DdefDOSXYZnrc code along with the phantom motion trace recorded with RADPOS. Dose values from MC simulations and measurements were found to be within 3.5% of each other. The passing rate for a gamma comparison of 3%/2 mm between Monte Carlo simulations and film measurements were found to be better than 98%. In conclusion, our 4D Monte Carlo simulations using the defDOSXYZnrc code accurately calculates dose delivered to a deforming anatomy. Future work will focus on irregular respiratory motion patterns.